2006
DOI: 10.1191/0143624406bse156tn
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation performance for spaces where smoking is permitted: a review of previous work and field study results

Abstract: This paper reviews previous studies and reports on the first stage of a series of field studies developed with the aim of assessing the performance of ventilation systems currently in use in public houses where smoking is permitted. Established ventilation theory is used to hypothesize the behaviour of these systems predicting that exposure to environmental tobacco smoke will be substantially reduced. The problems associated with conducting field studies in buildings of this nature are discussed, and the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…This conclusion is supported by recent results presented by the authors (Geens et al 2006) and further studies need to be undertaken to collect additional data before a definitive conclusion can be reached to what is a complex and multi-dimensional problem that has increasingly attracted emotional, highly biased and unscientific commentary. Study done in a isolated community with a single hospital.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…This conclusion is supported by recent results presented by the authors (Geens et al 2006) and further studies need to be undertaken to collect additional data before a definitive conclusion can be reached to what is a complex and multi-dimensional problem that has increasingly attracted emotional, highly biased and unscientific commentary. Study done in a isolated community with a single hospital.…”
Section: Resultssupporting
confidence: 76%
“…It is interesting to note that in the published results of a number of "before and after ban" studies (Tables 1-4), the levels of ETS markers such as carbon monoxide and fine particulates are comparable with those found in well ventilated venues before the ban (Geens et al 2006). Furthermore several of the authors of the papers reviewed suggest that further research is required to establish the extent to which smoke may migrate into the building from outside areas, rather than concluding that ventilation is equally effective.…”
Section: Discussionmentioning
confidence: 54%
“…A recent review on ventilation performance for spaces where smoking is permitted also identified conflicting views. The authors acknowledge that where attention has been paid to ensuring that the ventilation system being tested is adequate and working correctly, significant improvements in indoor air quality can be made, but such solutions need to be scientifically and critically evaluated (Geens et al, 2006). Previously, pro-technological studies have been criticised for applying an incorrect method of calculation and as a result reporting excessively high reduction percentages in ETS (see for example National Institute for Public Health and the Environment (2006) and Piha (2006)).…”
Section: Ventilation and Designated Smoking Areas With Ventilation Sy...mentioning
confidence: 99%
“…Pollutants generated from automobiles may accumulate in UPGs, and/or penetrate into the indoor environment [1,8,12]. Particulate materials (PM 10 , PM 2.5 ) within buildings are mostly derived from outdoor particles drawn in through HVAC systems [1,[13][14][15][16][17][18]. If the ventilation system is ineffective at completely discharging vehicle-induced pollutants from enclosed underground spaces, the pollutants can accumulate in these indoor environments and cause serious health effects in human beings [2,3,6,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%